Tunisia : 2015 Article IV Consultation, Sixth Review under the Stand-By Arrangement, and Request for Rephasing-Press Release; Staff Report; and Statement by the Executive Director for Tunisia. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Tunisia's economy has been resilient throughout a protracted political transition and a difficult international economic environment. The country has been facing headwinds from security threats and social tensions, which are offsetting the benefits from the successful conclusion of the political transition, lower international oil prices, and a recovering Europe. The banking system remains fragile, with the system's capital adequacy ratio below the minimum regulatory requirement. The medium-term prospects remain favorable, with growth projected to increase to 4.7 percent by 2020.